2005
DOI: 10.1007/s00125-004-1665-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of common polymorphisms in the HNF4? promoter on susceptibility to type 2 diabetes in the French Caucasian population

Abstract: Aims/hypothesis: The gene encoding HNF-4α, an orphan nuclear receptor playing critical roles in embryogenesis and metabolism by regulating gene expression in pancreatic beta cells, liver, and other tissues, is localised to chromosome 20q13, where linkage to type 2 diabetes has been shown in multiple studies. As two reports have independently demonstrated a convincing association with variants adjacent to the HNF-4α P2 promoter in Finnish and Ashkenazi Jewish populations, we evaluated their contribution to diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Interestingly, some of the diabetes-associated variants account for most of the evidence of linkage to chromosome 20q13 reported in these two populations. Consistent with these results, genetic variation near the P2 region of HNF4A is associated with T2D in other Danish and UK populations, but not in French or other Caucasian populations (83), which argues for genetic heterogeneity in HNF4A variants susceptibility. The causal variant(s) affecting the expression or function of HNF4␣ are still unknown and could result in a combination of relative insulin deficiency and defective regulation of the hepatic gluconeogenesis.…”
Section: Relevance Of Genes Involved In Monogenic Diabetes To Multsupporting
confidence: 74%
“…Interestingly, some of the diabetes-associated variants account for most of the evidence of linkage to chromosome 20q13 reported in these two populations. Consistent with these results, genetic variation near the P2 region of HNF4A is associated with T2D in other Danish and UK populations, but not in French or other Caucasian populations (83), which argues for genetic heterogeneity in HNF4A variants susceptibility. The causal variant(s) affecting the expression or function of HNF4␣ are still unknown and could result in a combination of relative insulin deficiency and defective regulation of the hepatic gluconeogenesis.…”
Section: Relevance Of Genes Involved In Monogenic Diabetes To Multsupporting
confidence: 74%
“…This observation is consistent with observations in many populations emphasizing the role of variants in HNF4A in the manifestation of T2D (Figure 1). 5,6,[19][20][21][22][23][24][25][26][27][28][29] Meta-analysis revealed that the trend for the elevated OR, as found here in North Indians, is seen in 10 other populations. Notably, rs1884613 has higher effect size in North Indians (OR¼1.35 (95%CI 1.17-1.54)) compared with pooled Scandinavian subjects (OR¼1.14 (95%CI 1.06-1.23)), lesser only to Ashkenazi population (OR¼1.70 (95%CI 1.23-2.38)).…”
Section: Discussionmentioning
confidence: 71%
“…However, the genetic variation of HNF4A in promoter 2 region is not associated with type 2 diabetes in the French Caucasian population [19]. It is possible that some genes other than HNF4A within the 20q13.12 region contribute to the development of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 92%